A review of case–control studies on the risk factors for the development of autoimmune blistering diseases. (5th October 2015) - Oh, D.D.; Zhao, C.Y.; Murrell, D.F.
Abstract: Autoimmune blistering diseases (AIBD) are a group of rare but potentially fatal diseases characterized by the production of autoantibodies directed against the structural proteins of the skin. Much has been published on the clinical manifestation and interventional options for AIBD, especially on the more common subtypes such as bullous pemphigoid, pemphigus vulgaris (PV) and pemphigus foliaceus (PF). However, the aetiology of AIBD remains unknown. We aim to provide an overview of published case–control studies focussing on the non‐genetic aetiological factors of bullous pemphigoid, PV and/or PF. The relevant studies were appraised for their validity and results. Our results showed that a large proportion of the studies had inconclusive results due to compromised study methodologies. Moreover, there were no identified case–control studies that investigated the possible associations between bullous pemphigoid and patient environment, or the potential links between pemphigus and drugs. Hence, a case–control study with a higher quality design addressing these shortcomings would contribute greatly to our knowledge of AIBD.